To find the number that makes the expression \( (-5 + __) + (8 \cdot 18) + c \) equivalent to \( c \), we can first simplify the expression step-by-step.
-
Calculate \( 8 \cdot 18 \): \[ 8 \cdot 18 = 144 \]
-
Plug in the calculation into the expression: \[ (-5 + __) + 144 + c \]
-
Combine constants (without the blank): To make the entire expression equal to \( c \), we set up the equation: \[ (-5 + __) + 144 + c = c \]
-
Rearranging gives: \[ -5 + __ + 144 = 0 \]
-
Combine constants: \[ -5 + 144 = 139 \] Therefore, we have: \[ 139 + __ = 0 \]
-
Solve for the blank: \[ __ = -139 \]
Thus, the number that makes the expression equivalent to \( c \) is \(-139\).